Peace Journalism in the Kanjuruhan Tragedy - Rosalina, Indah Fajar (Kalijaga Journal of Communication, 2023)
This research focuses on answering the question of how Metro TV and TVOne implemented peaceful journalism in the Kanjuruhan Stadium tragedy in October 2022. The incident, which killed 135 people and injured 583 people, then developed as a conflict between the police, match organizers, and football supporters, especially Aremania. In the news, conflict issues are always an exciting topic to discuss. Events that contain conflict naturally attract people and have more sales potential than mediocre events. Therefore, researchers are interested in examining how conflict is framed by the media, especially TV, from a Peace Journalism perspective. Using Descriptive Qualitative Research Methods with framing analysis Robert N. Entman 1) Define Problem, 2) Diagnose Causes, 3) Make a Moral Judgment (moral decision maker), 4) Treatment Recommendation (Problem-Solving) and the concept of peace journalism, namely orientation to truth, society, peace, and problem-solving. The results of this research indicate that from the four framing analysis units and the concept of peace journalism, it can be seen that TVOne has implemented three of the four fundamental concepts of peace journalism, namely oriented toward peace, society, and conflict resolution efforts. This is marked by highlighting issues that focus on victims and losses of conflict and providing space to talk to each figure in the conflict. Meanwhile, Metro TV, of the four components of peaceful journalism analysis, only 1 focuses on efforts to implement peaceful journalism, namely problem solving. Metro TV focuses more on efforts to find the cause of the conflict and resolve the conflict by blaming one particular party but does not focus on the deep sorrow of the victims.